Culture of rotifer Brachionus angularis Hauer feeding with dried Chlorella (University Journal of Zoology, Rajshahi University, 2008)
A study was carried out to know the performance of powdered dried Chlorella for culture of rotifer Brachionus angularis. B. angularis was fed with powdered dried Chlorella in treatment 1, live or fresh cultured Chlorella in treatment 2 and bakers yeast in treatment 3. The rage of physicochemical parameters during culture of rotifer such as water temperature, air temperature, pH and dissolved oxygen were within the suitable ranges for B. angularis culture and more or less similar in all the treatments. The highest population densities of B. angularis recorded in treatment 1, treatment 2 and treatment 3 were 50, 60 and 30 ind/ml, respectively. The mean population densities were 30.1±12.2, 37.4±14.6 and 21.1±6.1 ind./ml in treatment 1, treatment 2 and treatment 3, respectively. The results revealed that the powdered dried Chlorella had significant effect on the population density of B. angularis and was better than that of bakers yeast. So, when live Chlorella will not be available, powdered dried Chlorella can be successfully used as feed for B. angularis culture. Keywords: Rotifer, Chlorella, yeast, culture medium Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 73-76